Analisis Kemampuan Berpikir Kreatif Siswa SMP Bergaya Belajar Theoris dalam Mengajukan dan Memecahkan Masalah Bangun Ruang Sisi Tegak - Pranyata, Yuniar Ika Putri; Ferdiani, Rosita Dwi; Farida, Nur (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This study will reveal the analysis of creative thinking skills of junior high school students with theoretical learning styles in solving vertical side-space problems. The process of creative thinking includes students with a type of theoretical learning style. This student's creative thinking process can be seen from the behavior of students in posing and solving problems that can describe their mental actions. This research was conducted at SMP Al Inayah Purwosari Pasuruan. The research subjects were the 8th grade students of SMP Al Inayah Purwosari Pasuruan.Based on the research results it is known that the subject has fulfilled the aspects of novelty, fluency, and flexibility as indicators of creative thinking ability. The subject is able to fulfill the novelty aspect because it can cause problems that are different from the problems raised previously. The subject is able to fulfill aspects of fluency because it can cause problems that are diverse and different from other students. The subject is able to fulfill the aspect of flexibility because it uses a different solution than usual.